Project management with dotProject : implement, configure, customize, and maintain your dotProject installation : a complete beginner's guide to every aspect of setting up and administering your dotProject installation /: implement, configure, customize, and maintain your dotProject installation : a complete beginner's guide to every aspect of setting up and administering your dotProject installation. (2007) - Unknown
No abstract available